Motion Graphics Sebagai Media Edukasi Seksual Untuk Anak Usia Dini Mengenai Batasan Tubuh Kepada Orang Tua Di Kejawan Putih Tambak - Lutfiah Ismiati Rofiah; Bayu Setiawan (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
Cases of sexual violence against early childhood in Indonesia remain high, while children's understanding of body boundaries and parents' readiness to provide sexual education are still limited. This study aims to design an educational medium in the form of motion graphics to convey body boundary concepts to young children through parental guidance. The research employs a qualitative method with the Multimedia Development Life Cycle (MDLC) approach, which includes the stages of concept, design, material collecting, assembly, testing, and distribution. Data collection techniques consist of literature study, observation, and questionnaires conducted in the Kejawan Putih Tambak area. The findings indicate that children still have difficulty understanding body boundary concepts, while parents are aware of the importance of early sexual education but feel hesitant and uncomfortable delivering it. The developed motion graphics media is considered effective as it presents information in an engaging, communicative, and easily understandable way. Therefore, motion graphics can serve as an effective solution to assist parents in delivering sexual education to children from an early age.